Prediction of water and oil percolation thresholds of a microemulsion by modeling of dynamic viscosity using response surface methodology - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; Noor, I.M.; See, C.H.; Saphanuchart, W. (Elsevier, 2013)
This paper presents the application of Design of Experiments to predict water and oil percolation thresholds of a microemulsion using dynamic viscosity data as a function of water volume fraction. One-factor and historical data were the two investigated design types of response surface methodology. The models were validated and maximized. The predicted water and oil percolation thresholds using historical data design were close to their experimental values. The oil percolation threshold could be predicted more precisely using one-factor design than historical data design while one-factor design can capture the relationship between the response and design factor with fewer experimental data.